The philosophical dimensions of women’s intellectual agency in the works of Muriel Spark - Dzhalaldinova, M.Z. (Karaganda National Research University named after E.A. Buketov, 2025)
This article explores the philosophical dimensions of women’s intellectual capacity in the literary world of Muriel Spark. Through her innovative narrative strategies, writer illustrates themes of identity, autonomy, and the search for meaning in a fragmented postmodern world. The analysis focuses on how M. Spark’s female characters negotiate intellectual independence, moral choice, and self-definition, revealing the intersection of literature and philosophy in her representation of women’s inner lives.
Topical issues in the history and theory of philosophy = Философия тарихы мен теориясының өзекті мәселелері = Актуальные проблемы истории и теории философии
Keywords: women’s intellectual agency; the works of Muriel Spark; Muriel Spark; literary exploration; women's empowerment; satire; feminist literature; independence; individuality; education empowerment; gender stereotypes; philosophical dimensions; women’s intellectual capacity